2015
DOI: 10.1590/1678-775720140259
|View full text |Cite
|
Sign up to set email alerts
|

Host response mechanisms in periodontal diseases

Abstract: Periodontal diseases usually refer to common inflammatory disorders known as gingivitis and periodontitis, which are caused by a pathogenic microbiota in the subgingival biofilm, including Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Tannerella forsythia and Treponema denticola that trigger innate, inflammatory, and adaptive immune responses. These processes result in the destruction of the tissues surrounding and supporting the teeth, and eventually in tissue, bone and finally, tooth loss.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
320
0
28

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 374 publications
(349 citation statements)
references
References 268 publications
(440 reference statements)
1
320
0
28
Order By: Relevance
“…Alcoholics tend to also smoke tobacco that increases their risk for periodontal disease. Numerous studies showed associations between different periopathogens, the immune host response and chronic periodontitis [25]. Present of periopathogens: A. actinomycetemcomitans, P. gingivalis, T. forsythia and T. denticola are considered to be the main periodontal pathogens and strongly associated to the clinical status of periodontal tissues and progression of the periodontal disease [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Alcoholics tend to also smoke tobacco that increases their risk for periodontal disease. Numerous studies showed associations between different periopathogens, the immune host response and chronic periodontitis [25]. Present of periopathogens: A. actinomycetemcomitans, P. gingivalis, T. forsythia and T. denticola are considered to be the main periodontal pathogens and strongly associated to the clinical status of periodontal tissues and progression of the periodontal disease [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…DC has a central role in directing the T cell response. They can change to T helper cell (Th) 1, Th2, Th17 and T regulatory cells (Treg) [65]. Certain bacterial strains induce the production of Th polarizing key cytokines by DCs, such as IL-10, IL-12 and IL-23 [66,67].…”
Section: Probiotic Effect On Immune Responsesmentioning
confidence: 99%
“…They represent a family of human zinc-dependent endopeptidases [65]. L. brevis CD2 decreased MMP in saliva [60].…”
Section: Probiotic Effect On Immune Responsesmentioning
confidence: 99%
See 2 more Smart Citations